Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3389/frans.2023.1118749
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen deuterium exchange and other mass spectrometry- based approaches for epitope mapping

Abstract: Antigen-antibody interactions are a fundamental subset of protein-protein interactions responsible for the “survival of the fittest.” Determining the interacting interface of the antigen, called an epitope, and that on the antibody, called a paratope, is crucial to antibody development. Because each antigen presents multiple epitopes (unique footprints), sophisticated approaches are required to determine the target region for a given antibody. Although X-ray crystallography, Cryo-EM, and nuclear magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 263 publications
0
8
0
Order By: Relevance
“…For epitope mapping of antibodies and non-antibody sca↵olds, a variety of experimental methods have been employed, including X-ray crystallography, NMR, mass spectrometry, peptide arrays and deep mutational scanning-based approaches. [14][15][16][17][18][19][20][21][22] Computational methods have potential to be faster and less costly, however, even advanced artificial intelligence (AI)-based AlphaFold and RoseTTAFold [23][24][25][26] have faced challenges in accurately predicting protein-protein interactions. [27][28][29][30] While success cases exist, such as the model of a PD-L1/CD80 complex, 31 large screening studies have shown a low number of highly-accurate antibody-antigen complex prediction.…”
Section: Introductionmentioning
confidence: 99%
“…For epitope mapping of antibodies and non-antibody sca↵olds, a variety of experimental methods have been employed, including X-ray crystallography, NMR, mass spectrometry, peptide arrays and deep mutational scanning-based approaches. [14][15][16][17][18][19][20][21][22] Computational methods have potential to be faster and less costly, however, even advanced artificial intelligence (AI)-based AlphaFold and RoseTTAFold [23][24][25][26] have faced challenges in accurately predicting protein-protein interactions. [27][28][29][30] While success cases exist, such as the model of a PD-L1/CD80 complex, 31 large screening studies have shown a low number of highly-accurate antibody-antigen complex prediction.…”
Section: Introductionmentioning
confidence: 99%
“…To better resolve antibody-OspA interactions within Bin 1, five V H Hs were subjected to epitope mapping by hydrogen exchange (HX)-mass spectrometry (MS) analysis using protocols optimized for OspA (33, 44). HX-MS is an increasingly powerful tool for epitope mapping in which the HX reaction is conducted in solution and captures antibody-induced changes in antigen backbone flexibility; strong reductions in HX are interpreted as points of antigen-antibody contact (45). As predicted, HX-MS indicated that all five V H Hs in bin 1 protected regions within OspA’s central β-sheet (33).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen–deuterium exchange mass spectrometry (HDX-MS) is a widely used tool for investigating the dynamics of proteins and their interactions in vitro and promises to become a valuable tool for studies in vivo . For the biopharmaceutical discovery and development sector, HDX-MS data have become important for understanding interactions of proteins with covalently bound small-molecule drugs and also with large hydrogen-bonded protein and glycoprotein ligands, resulting in better understandings of their mechanism of action. HDX-MS data are used to substantiate and protect intellectual property, to support biologics license applications, and to evaluate the physicochemical similarity between a biosimilar candidate and the originator product. Most similarity comparisons are qualitative; however, scientists have made significant progress toward quantitative evaluations of HDX-MS data, including free energy determinations of biophysical processes. As HDX-MS measurement precision improves, quantitative evaluations may become ubiquitous.…”
Section: Introductionmentioning
confidence: 99%